Leptin and Leptin Resistance in the Pathogenesis of Obstructive Sleep Apnea: A Possible Link to Oxidative Stress and Cardiovascular Complications. (20th February 2018) - Berger, Slava; Polotsky, Vsevolod Y.
Abstract : Obesity-related sleep breathing disorders such as obstructive sleep apnea (OSA) and obesity hypoventilation syndrome (OHS) cause intermittent hypoxia (IH) during sleep, a powerful trigger of oxidative stress. Obesity also leads to dramatic increases in circulating levels of leptin, a hormone produced in adipose tissue. Leptin acts in the hypothalamus to suppress food intake and increase metabolic rate. However, obese individuals are resistant to metabolic effects of leptin. Leptin also activates the sympathetic nervous system without any evidence of resistance, possibly because these effects occur peripherally without a need to penetrate the blood-brain barrier. IH is a potent stimulator of leptin expression and release from adipose tissue. Hyperleptinemia and leptin resistance may upregulate generation of reactive oxygen species, increasing oxidative stress and promoting inflammation. The current review summarizes recent data on a possible link between leptin and oxidative stress in the pathogenesis of sleep breathing disorders.